Youth and skills putting education to work (EFA global monitoring report, 2012)
"Many young people around the world -- especially the disadvantaged -- are leaving school without the skills they need to thrive in society and find decent jobs. As well as thwarting young people's hopes, these education failures are jeopardizing equitable economic growth and social cohesion, and preventing many countries from reaping the potential benefits of their growing youth populations. The 2012 Education for All Global Monitoring Report examines how skills development programmes can be improved to boost young people's opportunities for decent jobs and better lives."--Publisher's description